Premature atrial contractions and their associations with cryptogenic strokes - Khan, Muhammad Kamran; Fayaz, Maheen; Raja Farhat Shoaib,; Waseem Tariq Malik,; Laiba Fayaz,; Saeedullah Shah, (Journal of the Pakistan Medical Association, 2025)
Objective: To assess the association between premature atrial contractions and cryptogenic stroke while comparing the prevalence of premature atrial contractions among cryptogenic and non-cryptogenic stroke patients. Method: The retrospective, cross-sectional study was conducted at the Shifa International Hospital, Islamabad, Pakistan, and comprised data from January 2020 to April 2021 of patients diagnosed with ischemic stroke on magnetic resonance imaging of the brain, and who underwent investigation and treatment according to the national stroke guidelines. Patients with cryptogenic stroke were placed in group A, and those with non-cryptogenic stroke in group B. Data on demographic information, stroke type, risk factors, and cardiac assessment was collected from the institutional electronic medical records. Data was analysed using SPSS 25. Results: Of the 118 patients, 44(37.3%) were in group A; 35(79.5%) males and 9(20.5%) females with mean age 64.09±12.28 years. There were 74(62.7%) patients in group B; 57(77%) males and 17(23%) females with mean age 65.56±12.12 years. Premature atrial contractions were detected in 43(97.7%) group A patients compared to 1 patient (2.3%) in group B (p<0.05), and demonstrated significant association with atrial fibrillation, dyslipidaemia, mitral stenosis and left ventricular systolic dysfunction (p<0.05) in group A, and with atrial fibrillation, previous myocardial infarction, left atrium dilatation, wall akinesia, left carotid artery stenosis, and left ventricular systolic dysfunction in group B (p<0.05). Conclusion: Prolonged cardiac monitoring pf stroke patients is critical to any effort to identify occult atrial fibrillation. Besides, premature atrial contractions were significantly associated with cardiac risk factors. Key Words: Atrial fibrillation, Stroke, Cryptogenic, Premature atrial contractions, Holter monitoring.